MEMANGGUNGKAN KISAH TANTRI ALIH WAHANA DALAM PERTUNJUKKAN PRAGMENTARI TANTRI GONG KEBYAR ANAK-ANAK DUTA KABUPATEN KLUNGKUNG, PESTA KESENIAN BALI 2018 - I Kadek Surya Jayadi (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
Tantri is one of the Balinese literature, which is well known and has its own impression. This special impression arises because of its substance, which makes animals the main figures in the storytelling and is rich in religious literary values. Because of the impression it gave, tantri works appeared in various forms. In addition, tantri literature is packaged in other works, one of which is the Tantri Dance Fragment. This study is a study of the fragmentary tantri